Autologous serum skin test in children - Godse Kiran (Wolters Kluwer Medknow Publications, 2008)
Chronic urticaria in children occurs less often than adults. Out of 17 children (age group 6-16 years, [Table 2]), six children (2 boys and 4 girls, 35%) showed a positive result in form of wheal and flare more than 1.5 mm than saline control.Autologous serum skin test is cheap, is easy to perform, and, if performed as appropriate, it has good sensitivity and even better specificity at detecting autoantibodies in children.